Identifying Code of Some Special Graphs - Enriquez, Enrico Limbo; Ranara, Jesus L.; Loquias, Carmelita N.; Estrada, Grace M.; Punzalan, Teodora J. (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
A subset S of V(G) is a dominating set of G if for every v V(G)S, there exists x S such that xv E(G). An identifying code of a graph G is a dominating set CV(G) such that for every vV(G), N_G[v]C is distinct. In this paper, we investigate the identifying code of some special graphs and give some important results.